Post-COVID fiscal rules: A central bank perspective - Sebastian Hauptmeier; Nadine Leiner-Killinger; Philip Muggenthaler; Stephan Haroutunian (European Central Bank (ECB), 2022)
Regarding a prospective reform of the European Stability and Growth Pact (SGP) it seems rather consensual that a simplified framework should take account of the prevailing macroeconomic context and enhance the balancing of sustainability and stabilisation considerations. This paper provides simulation analysis for the euro area and individual countries with a view to assessing the short- and longer-term budgetary and macroeconomic implications of a move to a two-tier system with an expenditure growth rule as single operational indicator linked to a debt anchor. Compared to the status quo, our analysis suggests that expenditure growth targets which take account of the ECB's symmetric 2% inflation target can improve the cyclical properties of the framework. Fiscal policy would be tighter when inflation is above the target but looser when inflation is below target, resulting in a better synchronisation of fiscal and monetary policies. Providing additional fiscal accommodation in a low inflation environment would enable monetary policy to operate more effectively especially in the vicinity of the effective lower bound. The link to a longer-term debt anchor at the same time ensures a transition towards the Treaty's debt reference level.
Keywords: E63; H50; H60; 330; European fiscal rules; monetary and fiscal policy interactions; debt sustainability